STUDY THE IMPACT ON THE IMPLEMENTATION OF LOCAL DEVELOPMENT PROJECTS. CASE STUDY: KHOK YANG RESERVOIR - Nunchui, Nucha; Chimhat, Pairat; Nunklam, Direk; Preecha, Nicharee; Wichakara, Phra Palad Thanwa (Journal of MCU Nakhondhat, 2023)
The objectives of this research article were to 1) study the environment in the reservoir construction area and other things that are continuous and important to villagers’ livelihoods; 2) study the operation characteristics of the Khok Yang Reservoir Construction Project, and 3) the impact that will occur on the environment and other things as stated in No. 1, if such a reservoir construction project is undertaken. lower in the district Mueang Nakhon Si Thammarat District using action research using interviews and focus groups. from key informants, including people in affected areas and groups that play an important role in decision-making. used for descriptive content analysis The results of the research were as follows: 1) Khok Yang Khlong community There is a livelihood of the Khlong Kok Yang community. with the relationship between the community and the ecosystem cause a culture of eating coexistence to have faith in the unseen Religion is a tool to hold the mind. There are wisdoms in making a career in agriculture, gardening, farming, livestock, fishery, and there are other plants that generate income for the villagers of Khlong Khok Yang community, such as betel nut, fruit tree, Somrom garden, Father Tao Garden, rubber plantation, and palm plantation. 2) Impact If Khlong Khok Yang Reservoir is built, the economy amounts to 317,800,000 million baht/year, the environment, ecosystems/soil, water, forest and wildlife resources that directly affect the soil condition which is lowland soil suitable for agriculture. And that affects forest plants. 3) Social, cultural and belief causes the kinship system to disappear. Because having to move to a new place of residence, relatives, brothers and sisters do not live together.